Another View at the Interaction of Poetry and Music in Jazeps Vitols’ Choral Works - Grauzdiņa, Ilma (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The aim of the research is to explore creation of musical form of Jazeps Vitols’ (1863-1948) most expanded a cappella choral works. Although Jazeps Vitols’ choral works have been discussed in monographs and in several scientific articles, the musical form of choral songs is offen individual, therefore students still have difficulties to determine the musical form of compositions, and this aspect provokes ardent discussions among experts. The author of the article bases her opinion first of all on a comprehensive analysis of the poem (images, language, dramaturgy, composition) set in the choral work and, secondly, on the comparison between results of analysis and implementation of these parameters in J. Vitols’ music. Such an approach lets to define more accurately the musical form of choral song – the total product born out of the cooperation of the two arts. Furthermore, such comprehensive view allows to reveal important characteristic features of individual style of the composer and stylistic details of musical compositions, understanding of which could be useful for performers – conductors and singers.